Proposed Model to Achieve Excellence in the Management of Educational Institutions in the State of Kuwait in the Light of Global Total Quality Management Models - Al-Harbi, Manal (The Arab Journal of Administration, 2023)
The Study Dealt With the Challenges of the Educational System Related to Achieving and Improving the Quality of Education, With the Aim of Achieving excellence in Kuwaiti pre-university education institutions, and reviewing the Frame of Reference for the Factors Affecting the Management of Pre-university Education in General, and the Criteria Used to Measure and Educational Achievements. The Study Problem Was Identified by Addressing the Challenges Facing the Education Administration, Pre-university in Kuwait, And a review of the frame of reference for the factors affecting the administration of pre-university education in general, and the criteria used to measure and achievements of education. The problem of the study was identified by addressing the challenges facing the administration of pre-university education in Kuwait. The problem has been identified in this question: “ How Can the Distinguished Educational Management Quality be Achieved in Kuwaiti Pre-university Education Institutions in the light of Comprehensive Quality Models?” The Study Adopted the Descriptive Approach, and Compared the Models Adopted in Quality in Terms of Methodologies, Mechanisms, Comparison Tools and Performance Measurement. It Also Dealt With: the Conceptual Framework, the Factors Affecting the Management of Educational Institutions, the Criteria Used to Measure Educational Achievements, the Measurement of Educational Efficiency and Productivity, Administrative Effectiveness, the Concepts of Total Quality Management, Quality Assurance and Control, the Culture of Quality in Education, and a Number of Global Models of Quality, and a Number of Results Were drawn. Of Which: 1- The Importance of the Qualified Human Resources Component in Improving all the Elements of Educational Systems. 2- All Models Agree on the Development Process and Performance Improvement as an Imperative. And it reached recommendations, including: Spreading a Culture of Total Quality, Issuing Periodic Bulletins in the Field of Modern Management, Providing the Administration With the Developments Around Them in the Field of Educational Quality, Building a Clear Institutional Strategy, in Addition to the Transparency Imposed by Work Reports and Dealing With Stakeholders Broadly.